POSTER PRESENTATION: Local and Regional Food Production and Food as Medicine - LaBonte, Kacey (UVM ScholarWorks, 2024)
Western and Indigenous practices intertwine in efforts to utilize food as medicine to improve food sovereignty and health outcomes. The Two-Eyed Seeing approach, articulated by Mi’kmaw Elder Albert Marshall, offers an illustrative model for leveraging both knowledge paradigms for the greater good. Our project links the Two-Eyed Seeing approach to aspects of food systems and overall resilience to realize cultural practice, personal and community health, and opportunities for new food markets. Our poster will discuss this project and delve into these two dimensions, with embedded interest in local and regional food production and gathering practices. The first dimension involves analysis of incorporating health-promoting and culturally relevant foods into medical contexts through produce prescriptions, food pharmacies, and medically tailored meals. The second dimension emphasizes the importance of Indigenous knowledge and practices in this space. From our research, we see the intersections of these two dimensions through broad community food systems development. Due to the growing desire to incorporate such practices in our food and health systems, there is a unique opportunity for farmers, healthcare providers, and food businesses to link the values of local and regionally produced food and connect their practices to healthcare systems. Food as medicine-related farming and business strategies reveal that these operations are impacted and informed by the challenges posed by concurrent public health crises and climate disruption. Recognizing the interconnectedness of these issues, we have come to understand that any effective approach to food as medicine must consider resilience efforts within the broader context of food systems. In this poster, we will share the current state of our work with a focus on the intricate relationships between food, health, and resilience, and outline our plans for future food as medicine initiatives. https://scholarworks.uvm.edu/fss2024/1028/thumbnail.jpg